Phytase Production by Aspergillus niger CFR 335 and Aspergillus ficuum SGA 01 through Submerged and Solid-State Fermentation. (29th January 2014) - Shivanna, Gunashree B.; Venkateswaran, Govindarajulu
Abstract : Fermentation is one of the industrially important processes for the development of microbial metabolites that has immense applications in various fields. This has prompted to employ fermentation as a major technique in the production of phytase from microbial source. In this study, a comparison was made between submerged (SmF) and solid-state fermentations (SSF) for the production of phytase from Aspergillus niger CFR 335 and Aspergillus ficuum SGA 01. It was found that both the fungi were capable of producing maximum phytase on 5th day of incubation in both submerged and solid-state fermentation media. Aspergillus niger CFR 335 and A. ficuum produced a maximum of 60.6 U/gds and 38 U/gds of the enzyme, respectively, in wheat bran solid substrate medium. Enhancement in the enzyme level (76 and 50.7 U/gds) was found when grown in a combined solid substrate medium comprising wheat bran, rice bran, and groundnut cake in the ratio of 2 : 1 : 1. A maximum of 9.6 and 8.2 U/mL of enzyme activity was observed in SmF by A. niger CFR 335 and A.ficuum, respectively, when grown in potato dextrose broth.